2015
DOI: 10.3389/fbioe.2015.00170
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Protein–Protein Interfaces through a Protein Contact Network Approach

Abstract: Anthrax toxin comprises three different proteins, jointly acting to exert toxic activity: a non-toxic protective agent (PA), toxic edema factor (EF), and lethal factor (LF). Binding of PA to anthrax receptors promotes oligomerization of PA, binding of EF and LF, and then endocytosis of the complex. Homomeric forms of PA, complexes of PA bound to LF and to the endogenous receptor capillary morphogenesis gene 2 (CMG2) were analyzed. In this work, we characterized protein–protein interfaces (PPIs) and identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…The integrated computational approach disclosed active zones in the SARS-CoV and SARS-CoV2 complexes with the ACE2 ectodomain. These active zones, as demonstrated in previous studies 41,60,61 and in the present research by the convergence among different approaches, have an extremely high probability of acting as allosteric sites, which can modulate spike/ACE2 protein binding.…”
Section: ■ Conclusionsupporting
confidence: 80%
“…The integrated computational approach disclosed active zones in the SARS-CoV and SARS-CoV2 complexes with the ACE2 ectodomain. These active zones, as demonstrated in previous studies 41,60,61 and in the present research by the convergence among different approaches, have an extremely high probability of acting as allosteric sites, which can modulate spike/ACE2 protein binding.…”
Section: ■ Conclusionsupporting
confidence: 80%
“…In case of the protein backbone network (PBN), Cα atoms are generally considered as the representative of nodes and a distance of about 6.5 Å or less (based on the radial distribution of Cα atoms in protein structures) between any two sequentially non-adjacent residues are considered as an edge (Miyazawa and Jernigan, 1985;Patra and Vishveshwara, 2000). The construction and application of PBN have been extensively discussed in earlier reviews (Greene, 2012;Di Paola et al, 2015). Here, our focus is on the technical details of construction and the subsequent application of amino acid side-chain-based protein structure networks denoted as PScN (or PSN).…”
Section: Protein Structure Network Based On Backbone (Pbn) and The Simentioning
confidence: 99%
“…High P residues are spotted in the structure and mostly (but not necessarily) placed in the interchain region. In previous works [ 35 , 37 , 51 , 75 ], we demonstrated that the participation coefficient P addresses the functional role of residues in protein binding and, in general, identifies residues with a key role in protein structural and functional features.…”
Section: Resultsmentioning
confidence: 78%
“…The analysis was performed by means of a purposed software implemented in Matlab environment v 2014a, including functions from Bioinformatics Toolbox. Heat maps of P variation (comparison between holo and apo forms), Guimerà-Amaral cartography and clusters onto the protein ribbon representation, have been produced by means of a purposed Python script compiled in the embedded Python environment; for further details and application of the method see [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation